Developing sociocultural competence at the master student level: challenges and opportunities - Muntian, Svitlana; Мунтян, Світлана Геннадіївна; Мунтян, Светлана Геннадиевна; Valentinova, L. K.; Валентінова, Л. К. (My University, 2010)
EN: The importance of sociocultural competence for modern university graduates is universally acknowledged. Yet, in practical terms, developing this competence still poses a number of challenges related to background competence of master students and availability of academic hours. While information sources on relevant topics abound, there remains a deficit of comprehensive training packages that are finely attuned to the unique needs of master students in agricultural universities. UK: В статті проаналізовано теоретичні аспекти формування соціокультурної компетенції у студентів в процесі навчання їх англійської мови, узагальнено практичний досвід роботи зі студентами магістратури, презентовано власне бачення шляхів формування соціокультурної компетенції у цієї категорії суб′єктів навчання.
Keywords: соціокультурна компетенція; самоосвіта; технології викладання; начальні стратегії; форми усної комунікації